2014
DOI: 10.1002/2013je004563
|View full text |Cite
|
Sign up to set email alerts
|

Ice melting and downward transport of meltwater by two‐phase flow in Europa's ice shell

Abstract: With its young surface, very few impact craters, and the abundance of tectonic and cryovolcanic features, Europa has likely been subjected to relatively recent endogenic activity. Morphological analyses of chaos terrains and double ridges suggest the presence of liquid water within the ice shell a few kilometers below the surface, which may result from enhanced tidal heating. A major issue concerns the thermal/gravitational stability of these water reservoirs. Here we investigate the conditions under which wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 77 publications
(128 reference statements)
5
73
0
Order By: Relevance
“…Our results suggest that it is mainly the thermal state and the viscosity structure of the ice layer underneath the fault that control the development of the R‐T instabilities, the threshold value of viscosity being approximately 5 × 10 13 Pa s. Once viscosity in the zone underneath the fault drops below this value, the R‐T instabilities form and drain meltwater efficiently to the base of the shell. In this regard, our findings are complementary to those of Kalousová et al [], where the importance of the thermal state is stressed for an alternative drainage mechanism—the two‐phase flow. In Kalousová et al [] this mechanism is reported to allow for very effective meltwater drainage once the temperature in the ice shell reaches the pressure‐melting point in the whole zone underneath the reservoir, and the melt fraction exceeds the percolation threshold.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our results suggest that it is mainly the thermal state and the viscosity structure of the ice layer underneath the fault that control the development of the R‐T instabilities, the threshold value of viscosity being approximately 5 × 10 13 Pa s. Once viscosity in the zone underneath the fault drops below this value, the R‐T instabilities form and drain meltwater efficiently to the base of the shell. In this regard, our findings are complementary to those of Kalousová et al [], where the importance of the thermal state is stressed for an alternative drainage mechanism—the two‐phase flow. In Kalousová et al [] this mechanism is reported to allow for very effective meltwater drainage once the temperature in the ice shell reaches the pressure‐melting point in the whole zone underneath the reservoir, and the melt fraction exceeds the percolation threshold.…”
Section: Discussionsupporting
confidence: 86%
“…However, the methodology developed for terrestrial glaciers cannot be directly applied to planetary ice shells due to number of important differences in the physical setting. These include the absence of subglacial drainage system, closure of the hydrological network from above, limited crack initiation, insufficient meltwater supply, and 1 order of magnitude difference in the thicknesses of ice layers [ Kalousová et al , ]. Although hydrofracturing cannot be completely ruled out as one of the drainage mechanisms operating on Europa, we do not consider it in this study, mainly due to the lack of observational constraints on the drainage system within the ice shell.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological analyses of chaos terrains [ Schmidt et al , ] and double ridges [ Dombard et al , ] suggest the presence of shallow lenses of water or brines, perched only a few kilometers below Europa's cold brittle surface. However, it is not clear if liquid water can accumulate in the upper part of Europa's ice shell for long enough [e.g., Tobie et al , ; Kalousová et al , , ]. Nevertheless, recent detections of water vapor over Europa's south pole [ Roth et al , ; Sparks et al , ] suggest the existence of an ongoing plume activity similar to that observed at Enceladus [e.g., Hansen et al , ], and detection of salts [ McCord et al , ; Brown and Hand , ] and hydrated sulfuric acid [ Carlson et al , ] on Europa's surface indicates the presence of chemical elements essential for biology.…”
Section: Introductionmentioning
confidence: 99%